The Effect of PBL Learning Model Combined with Rewards and Punishment on Science Learning Outcomes - Yudhatami, Annisa Tri; Djumadi, D (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
This study aims to determine the effect of PBL learning model combined with rewards and punishments on the science learning outcomes of class VII students at SMP Muhammadiyah Sinar Fajar Cawas. This study used an experimental method with a pretest-posttest control group design. This study used a control class (VII As-Syifa) totaling 14 students and an experimental class (VII Al-Qolam) totaling 15 students. The research instrument was in the form of questions and observation sheets. Analysis of learning outcomes data using independent t-test with normality test and homogeneity test. The results of the research show that the three aspects of learning outcomes have an influence on this research. The results of the calculation of cognitive aspects using the independent t-test obtained Sig.(2-tiles) 0.001<with a significance level of 5% so that Ho was rejected and Ha was accepted. The results of the calculation of the affective aspect using the independent t-test obtained Sig.(2-tiles) 0.030<with a significance level of 5% so that Ho is rejected and Ha is accepted. The results of the calculation of the psychomotor aspect using the independent t-test obtained Sig.(2-tiles) 0.000<with a significance level of 5% so that Ho was rejected and Ha was accepted. This means that there is an influence of PBL learning model combined with rewards and punishments on the science learning outcomes of class VII students at SMP Muhammadiyah Sinar Fajar Cawas.